Knowledge, Attitude, and Practice of Doctors in Emergency Department Towards Antimicrobial Stewardship and Their Predictors in Tertiary Hospital in Kota Bharu, Kelantan - Bundan, Merayang (2020)
Introduction Antimicrobial stewardship (AMS) is vital in the Emergency Department (ED) because the doctors encounter high frequency of infectious disease. Therefore, we aim to measure the level of knowledge, attitude, and practice (KAP) of doctors towards AMS and their predictors in tertiary hospitals in ED, Kota Bharu, Malaysia. Method This cross-sectional study was conducted at the ED of Hospital Universiti Sains Malaysia and Hospital Raja Perempuan Zainab II in Kota Bharu, Malaysia, among 150 doctors from August 2019 to February 2020 using a previously validated self-administered questionnaire. Respondents were randomly selected. The questionnaire comprised of four sections, including sociodemographic, knowledge, attitude and practice on core elements of AMS. Descriptive statistics were used for data analysis. Multiple linear regression analysis was conducted to determine the best model of predictors of the KAP scores. Results The respondents' overall knowledge and practice were good but with an unfavourable attitude towards AMS with a mean percentage score of 85.3%, 70.4 %, and 58.1%, respectively. Multiple linear regression analysis revealed that the mean score of attitudes was associated with the doctor's years of overall ED experience (=0.198; p=0.003) and frequency of antibiotic prescription (=0.928; p=0.005). Doctors perceptions of AMS exhibited significant association with good knowledge (=0373; p=0.044) and good practice (=0.921; p=0.001) on AMS. Conclusions The respondent's overall knowledge and practice level was good but had an unfavourable attitude toward AMS. Significant predictors of good knowledge and practice were doctor's perceptions of AMS. The predictors of favourable attitudes toward AMS were antibiotic prescription frequency and years of ED experience.